Nitric oxide is involved in the brassinolide-induced adventitious root development in cucumber - Yutong Li (BMC Plant Biology, 2020)
Abstract Background Brassinolide (BR), as a new type of plant hormones, is involved in the processes of plant growth and stress response. Previous studies have reported the roles of BR in regulating plant developmental processes and also response tolerance to abiotic stresses in plants. The main purpose of our study was to explore whether nitric oxide (NO) plays a role in the process of BR-induced adventitious root formation in cucumber (Cucumis sativus L.). Results Exogenous application of 1 μM BR significantly promoted adventitious rooting, while high concentrations of BR (2–8 μM) effectively inhibited adventitious rooting. NO donor (S-nitroso-N-acerylpenicillamine, SNAP) promoted the occurrence of adventitious roots. Simultaneously, BR and SNAP applied together significantly promoted adventitious rooting and the combined effect was superior to the application of BR or SNAP alone. Moreover, NO scavenger (c-PTIO) and inhibitors (L-NAME and Tungstate) inhibited the positive effects of BR on adventitious rooting. BR at 1 μM also increased endogenous NO content, NO synthase (NOS-like) and Nitrate reductase (NR) activities, while BRz (a specific BR biosynthesis inhibitor) decreased these effects. In addition, the relative expression level of NR was up-regulated by BR and SNAP, whereas BRz down-regulated it. The application of NO inhibitor (Tungstate) in BR also inhibited the up-regulation of NR. Conclusion BR promoted the formation of adventitious roots by inducing the production of endogenous NO in cucumber.